2018
DOI: 10.1002/marc.201800138
|View full text |Cite
|
Sign up to set email alerts
|

A Robust, Self‐Healable, and Shape Memory Supramolecular Hydrogel by Multiple Hydrogen Bonding Interactions

Abstract: A versatile double-network (DN) hydrogel with two noncovalent crosslinked networks is synthesized by multiple hydrogen bonding (H-bonding) interactions. The DN hydrogels are synthesized via a heating-cooling photopolymerization process by adding all reactants of agar, N-acryloyl glycinamide (NAGA) and N-benzylacrylamide (NBAA) monomers, UV initiators to a single water pot. Poly(N-acryloyl glycinamide-co-N-benzyl acrylamide) (P(NAGA-co-NBAA)) with a triple amide in one side group is synthesized via UV-light pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 34 publications
(58 reference statements)
1
70
0
Order By: Relevance
“…Both these shifts indicate the H‐bonds interaction between NH and CO species. Whereas the smaller wavenumber shift of CO and NH stretching absorptions in HB‐PNAGA hydrogel during temprature increase suggests its stronger hydrogen bonding interaction . The above results demonstrate that HB‐PNAGA hydrogels were more stably cross‐linked by hydrogen‐bonded supramolecular interactions than linear PNAGA counterparts.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Both these shifts indicate the H‐bonds interaction between NH and CO species. Whereas the smaller wavenumber shift of CO and NH stretching absorptions in HB‐PNAGA hydrogel during temprature increase suggests its stronger hydrogen bonding interaction . The above results demonstrate that HB‐PNAGA hydrogels were more stably cross‐linked by hydrogen‐bonded supramolecular interactions than linear PNAGA counterparts.…”
Section: Methodsmentioning
confidence: 75%
“…Many supramolecular hydrogels have been developed for biomedical applications thus far . The supramolecular hydrogel, also known as “reversible hydrogel,” features dynamic physical interactions, such as host–guest, metal–ligand coordination, ionic, hydrophobic, and H‐bonding interactions, endowing the physical network with self‐healability, thermoplasticity, and thermoprocessability. However, it is noted that most of the supramolecular hydrogels suffer from poor mechanical properties and low stability, cannot bear a tensile, compressive, or tearing force, and only survive under the rheological test.…”
Section: Methodsmentioning
confidence: 99%
“…[ 20–23 ] These smart functions have been achieved by a sophisticated and intricate combination of the characters of the polymer main chain and cross‐linkers; therefore, this has enabled the versatile utilization of these hydrogels in a variety of biomedical, sensor, and soft actuator materials. [ 24–39 ] Consequently, this relatively new field has grown rapidly over the last decade. Thus far, various stimuli‐responsive and reversible cross‐linkers have been employed for this purpose, which include hydrophobic association, [ 24,25 ] hydrogen bonding, [ 26–29 ] dipole–dipole interaction, [ 30,31 ] metal–ligand/host–guest interactions, [ 32–34 ] and their combination with covalent closs‐linkages.…”
Section: Figurementioning
confidence: 99%
“…Thus, a multiple noncovalent cross-linked network could be more advantageous for designing self-healing materials with high mechanical properties. A double network based poly(N-acryloyl glycinamide-co-Nbenzyl acrylamide) containing a triple amide in one side group was reported by Feng et al The triple amide based soft material demonstrated a good shape memory ability, high mechanical strength (1.1 MPa) and about 95% self-healing efficiency at room temperature (Feng et al, 2018).…”
Section: Strategies To Synthesize Soft Self-healing Nanocomposites Phmentioning
confidence: 99%